Primary Renal Lymphoma Presenting as End-Stage Renal Disease. (2nd October 2017) - Butani, Lavjay; Ducore, Jonathan
Abstract : Primary renal lymphoma is a rare entity, even more so in children. Children with primary renal lymphoma present with variable clinical features such as constitutional signs and symptoms, acute kidney injury, palpable abdominal masses, and gross hematuria. Herein we report a child who presented with seemingly advanced chronic kidney disease and was eventually diagnosed with primary lymphoma. He responded well to intensive chemotherapy and recovered renal function, although he was left with some functional limitations as a consequence of his treatment regimen. Our report highlights the importance of keeping neoplastic conditions under consideration when taking care of children with severe kidney disease of unclear etiology.